Pemberhentian Tidak Hormat Aparatus Sipil Negara Dalam Kasus Tindak Pidana Korupsi - Biahimo, Jaqub; Kadir, Yusrianto; Bunga, Marten (Journal Evidence Of Law, 2023)
To Analyze the Regulation of Fish Theft and FAD Settlement According to the Provisions of Indonesian Legislation. To Analyze the Criminological Review of the Enforcement of Theft and Damage to FADs.In this study the author, using Empirical research methods. The data sources used in this research are primary and secondary data. The author uses direct observation and interview data collection techniques. In this research, the author analyzes the data using quantitative methods, namely analyzing the data and providing relevant explanations, the problem is discussed further research and analysis is carried out and makes it a conclusion. The problem in Gentuma Subdistrict is that some fishing boats have more FADs than the regulations stipulated in the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 18 of 2021 so that when there is a problem of fish theft, it cannot be processed because the procedure for releasing fishermen's FADs has violated the rules. Facts have shown that fisheries crime has become a very threatening act to Indonesia's natural resources because it has a detrimental impact on society and the state. This is a threat to the survival of the community and the state because it can damage the environmental ecosystem and also damage the existence of living things in the sea.